Role of Leader-Member-Exchange (LMX) in Improving Teacher Creativity - Tetrasari, Lusi; Komariah, Aan; Nurdin, Diding; Kurniady, Dedy Achmad; Salsabil, Syifa Hanifa; Permana, Riyaldi Dithia (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research examines the role of LMX in improving teacher creativity conducted by principals by using LMX theory. This research studies whether the principals show their maximal role in LMX and participate, empower, and collaborate with teachers to improve and increase school quality. So far, there are no apparent effects of LMX on teacher creativity. We try to examine the relationship between creativity and the role of LMX as a source of relations for teachers. The data were collected from 165 teachers and 19 principals in the Education Office in Bandung City, Indonesia. The statistical analysis used in this study is Partial Least Square (PLS) with smartPLS 3.0 software. We found out that LMX still has adverse effects when the principals have regulated and limited their participation, empowerment, and collaboration in LMX, so they have obstacles in showing their creativity. Through this research, we expect that the LMX practices based on professional effect, loyalty, contribution, and respect will greatly benefit teacher creativity; thus, principals must improve their communication and setting of shared works. Results of this research propose that friendship, mutual shares with good interpersonal communication, participation, empowerment, and collaboration are important aspects for principals to stimulate creativity.